Practice Guidelines: Addressing Vestibular and Visual Problems in the Neurologically Impaired Adult - Mary Jo McGuire (Scholarworks @ WMU, 2022)
The visual and vestibular problems experienced by adults post brain injury (concussion, traumatic brain injury, cerebral vascular accident, tumor removal, etc.) must be evaluated and treated in conjunction with each other for best outcomes. The American Occupational Therapy Association's (AOTA) Practice Framework categorizes both the visual and vestibular sensory systems as client factors (body functions) that are a part of the scope of practice of occupational therapy (AOTA, 2020). AOTA's statement on vestibular impairment, vestibular rehabilitation, and occupational performance emphasizes the importance of occupational therapists addressing this critical client factor. The skills of entry-level and advanced-level occupational therapists are outlined in that document (AOTA, 2017). The objective of this article is to provide practical guidance to support advanced-level occupational therapists in more careful analysis of vestibulo-ocular skills that are needed for safe and efficient occupational performance. Literature and conceptual models from 1986 to 2021 from the fields of occupational therapy, physical therapy, ophthalmology, optometry, audiology, neurology, and otolaryngology that address the visual and vestibular problems experienced by adults with traumatic brain injury were reviewed and compared. Two models are presented to provide a framework to guide occupational therapy assessment and intervention of clients with neurological disorders who have vestibulo-ocular deficits that interfere with occupational performance.